Reflections on Letters to my Countrymen - Momoh, Tony. (Lagos : EFUA Media Associates, 1993)
"Reflections On Letters To My Countrymen" provides in one volume for the first time the eleven landmark letters which Prince Tony Momoh wrote between April 1988 and August 1990 when he served in the Babangida Administration as Minister of Information.
osa; 11/04/18
Loans
Keywords: Food supply; Nigeria; Nigeria; Nigeria